CONSTITUTIONAL RIGHTS FOR PERSONS WITH DISABILITIES IN INDONESIA: PRESENT AND FUTURE REGULATIONS (A Comparative Perspective between Indonesia and Malaysia) - Djangko, Indri Sukmawati (Brawijaya Law Journal, 2015)
Recognition of similar rights between persons with disabilities and common people has become a global issue. The world has been realized this point and initiated some international programs to fight the rights for persons with disabilities. Indonesia has already recognized the disabilities people rights in constitution and other regulation. Contrary to the fact that the awareness of human right fulfillment for person with disabilities is already contained in Indonesian regulations, its realization is not enough to guarantee the welfare and human rights fulfillment for every person with disabilities. Through library research which is used as a method of data collection in this paper, the author compares the fulfillment of human rights for persons with disabilities in Indonesia and Malaysia. In this paper, the author explains constitutional rights that support the human rightsâ€™ existence for persons with disabilities, as well as describes the rights that are mandated in every level of regulation hierarchy that specifically regulating persons with disabilities. In the end, this paper also suggests alternative solution for Indonesia in the future.Â Keywords: disabilities, rights, Indonesian Law, Malaysian Law